Evaluation of shelf life of mango fruit using aloe vera coating and hot water treatment during storage - Noor Anisah Atirah Binti Zainalaabidin (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Shelf life is the time between initial of ripening (end of green life) until the remnant of saleable of edible life of the fruits. Shelf life is the time period that a yield can be relied upon to continue up a value quality level under specified storage conditions. Mango fruit confronts a number of troubles such as suffering a short shelf life, assault of microorganisms, mismanagement during storage and shipping. Therefore, postharvest losses of fruits give a grievous problem. The use of Aloe Vera gel as an edible coating has been reported to prolong the shelf life and delay senescence. Beside, hot water (HW) treatment can control postharvest diseases. The previous studies revealed that different techniques of HW treatment and Aloe Vera coating have been applied for improvement or maintenance of the shelf life and quality of fruits during shelf life period. However, the combination of different concentration of Aloe Vera coating and HW treatment of mango, especially of the Sunshine Mango were not adequately investigated. In this experiment, the various concentration of Aloe Vera coating combine with different HW temperature was used. Based on the result, Aloe Vera coating with 75% concentration and HW treatment with temperature 50Ccan be applied for improved or maintenance of the shelf life and quality of fruits during shelf life period.